Chemical Components and Cardiovascular Activities of Valeriana spp. (16th December 2015) - Chen, Heng-Wen; Wei, Ben-Jun; He, Xuan-Hui; Liu, Yan; Wang, Jie
Abstract : Valeriana spp. is a flowering plant that is well known for its essential oils, iridoid compounds such as monoterpenes and sesquiterpenes, flavonoids, alkaloids, amino acids, and lignanoids. Valeriana spp. exhibits a wide range of biological activities such as lowering blood pressure and heart rate, antimyocardial ischemia reperfusion injury, antiarrhythmia, and regulation of blood lipid levels. This review focuses on the chemical constituents and cardiovascular activities of Valeriana spp.